PENDIDIKAN BERBASIS KECERDASAN RUHANIAH (MEMBENTUK INSAN PARIPURNA/ INSAN AL-KAMIL) - Deswita Deswita (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2010)
This article aims at analyzing spiritual intelligence based education since the basically, the goal of education is to build perfect human (insan kamil). Such goal can be realized as long as the pupils are able to integrate all of their potential intelligences. Those potentials are physical, emotional, intellectual and spiritual intelligences. The integration of those intelligences is called spiritual intelligence. Furthermore, spiritual intelligence based education basically encourages the pupils to apply the values of spiritual (ilahiyat) in establishing relationship among humans and other creatures on the basis of God’s mercy.Kata kunci: pendidikan, kecerdasan ruhaniah